Limestone particle size and artificial light for laying hens in the second laying cycle - Alexsandro Nunes de Oliveira; Ednardo Rodrigues Freitas; Thales Marcel Bezerra Filgueira; Carlos Eduardo Braga Cruz; Germano Augusto Jerônimo do Nascimento (Revista Brasileira de Zootecnia, 2013)
The experiment was conducted to evaluate the effects of limestone particle size and the use of artificial light for laying hens in the second laying cycle. We used 240 Hisex White laying hens at 82 weeks of age in a completely randomized design in a 5 × 2 factorial arrangement, resulting in 10 treatments with 4 replicates of 6 birds. The variables were the five particle sizes obtained by increasing the proportion of thick limestone (0, 25, 50, 75 and 100%) compared with thin limestone and two lighting programs: with and without artificial light. Limestone particle size and light did not affect performance or egg quality. However, there were changes in bird feeding schedule throughout the day as a response to the lighting program. Bone quality, density and mineral content of the tibia were not affected by the treatments, but limestone particle size had a quadratic effect of on bone deformity and strength, obtaining maximum inclusion points with 63% and 59% of thick limestone, respectively. The use of large particles of limestone in the diet and the use of a lighting program does not influence the performance and quality of the eggs of laying hens in the second production cycle, but the use of a proportion of 63.3 g of average particle size (0.60 mm) replacing the fine limestone (0.23 mm) per 100 g of total limestone added to the diet improves bone quality in these birds.